ISLAMIC CRIMINAL LAW ON CHILD PROTECTION: ADDRESSING PARENTAL MALTREATMENT IN TANAH KARO - Alfarizi, Ilham; Ramadani (Al-Risalah, 2024)
This research aims to examine the application of Islamic criminal law in cases of child maltreatment by parents and assess the effectiveness of law enforcement by the Tanah Karo Police, specifically in relation to Law No. 35 of 2014 on Child Protection. The study seeks to highlight the alignment between Islamic law principles, which emphasize the protection of children, and Indonesia’s legal framework for child welfare. A qualitative approach was employed using a case study design. Data were collected through in-depth interviews, observations, and document analysis, providing comprehensive insights into the legal and social aspects of child maltreatment cases handled by the Tanah Karo Police. Findings indicate that Islamic criminal law views child maltreatment as a severe offense, prescribing punishments such as diyat (financial compensation) or hudud (fixed penalties) depending on the severity of the abuse. The Tanah Karo Police, in adherence to Article 76C of Law No. 35 of 2014 on Child Protection, has established collaborative efforts with the Office for Women's Empowerment and Child Protection as well as the Karo District Social Services to address and mitigate child maltreatment cases. This study provides a unique perspective on the integration of Islamic criminal law principles with national child protection laws, underscoring the role of law enforcement in bridging cultural, religious, and legal frameworks to protect children. The findings suggest that integrating Islamic law principles into the enforcement of child protection laws may strengthen the legal and moral mandate for child welfare, encouraging a more cohesive approach across different sectors of Indonesian society. This integration has the potential to improve collaboration between law enforcement and social services in cases of child maltreatment, enhancing support for victims and accountability for offenders.